ANALISIS HILANGNYA PENDAPATAN INSTALASI FARMASI AKIBAT PEMBELIAN RESEP PASIEN UMUM INSTALASI RAWAT JALAN DI LUAR RSUD SEKARWANGI KABUPATEN SUKABUMI - , DEWI HERMALIA, DR. Dra. Erna Kristin, Msi., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: RSUD Sekarwangi as a health institution recently that had changed into BLUD was certainly changing its operational activities to increase income without ignoring humanity values and patient safety. Pharmacy installation as the highest revenue resources in RSUD Sekarwangi should have main priority in hospital effort to increase revenue though coming prescription to IFRS. Within changing of visiting trend form inpatient to outpatient, number of visiting outpatirnt in RSUD Sekarwangi increased. However, in the fact, data shown that number of prescription came to IFRS was unbalanced with the number of visiting outpatient. Number of prescription coming out from pharmacy installation was quite high, reach 48%, with the assumption that all patient got prescription. If this situation was ignoring, certainly, it will influence the amount of hospital income from the hospital potential income. Objective: There were two sub objectives in this research. The first one is to evaluate number of actual general outpatientsâ prescription that coming out from outpatient pharmacy installation and income value that away from IFRS. The second one is to look for the influence factors that cause prescription coming out from pharmacy installation of RSUD Sekarwangi, in the point of view of 7P variable in marketing mix. Method: This research was observational research with design of cross sectional. Data was collected from whole prescription of general outpatient for 5 working days and the questionnaire that distributed to respondent randomly in the same day when they visit. Number prescription coming out from and coming in to IFRS was recorded together. Selected sample was carried out with the method of simple random sampling. With the criteria of general outpatient it involved 146 respondents. Questionnaire data was counted using Linkert scale method and analysis process using Chi-square and Simple t-test. Result: From 456 sheets of prescription written by doctor, there was only 57% prescription coming in to RSUD Sekarwangi Pharmacy, i.e. there were 194 sheets of prescription coming out with the value away of Rp 21.757.414. With the calculation of t-test, it shows that perception on RSUD Sekarwangi pharmacy from the two groups has significant difference on variable of promotion, meanwhile the perception on the outside pharmacy has significant difference on variable of people. Conclusion: Number of prescription coming out from RSUD Sekarwangi was quite high which is the main reason of patient purchasing drug from outside hospital because lack of promotion from the hospital. It was suggested to the hospital management to increase promotion effort and to educate patient to emerge prescription with the guaranty on the availability and safety drug. A suggestion that cover all prescription service is using one door system and developing electronic prescribing method. Keyword: 7P, prescription coming out, perception, hospital pharmacy installation